Working in the Public Sector. Introduction to the Thematic Issue - Kamp, Annette; Klemsdal, Lars; Gonäs, Lena (Nordic Journal of Working Life Studies, 2013)
Work in the public sector has been changing dramatically in recent decades. Reforms aimed at increasing the efficiency of public services have been extensive in the Nordic countries and elsewhere since the 1980s. The reforms and changes have to a large extent been associated with so-called New Public Management (NPM) principles, emphasizing the market as a central coordination mechanism. Consequently, public institutions have been restructured, their services are standardized and commodified, and market-like relationships between them have been created. In order to create markets and transform citizens into customers on a market, outsourcing and privatization have been stimulated (Blomqvist & Rothstein 2000, Busch et al 2005, Christensen & Lægreid 2007, Greve 2003). At the same time, traditional Weberian bureaucratic principles are still viable and even enhanced within the sector, for instance, as a consequence of the use of contracts as a means of managing public organizations (Greve 2008). Lately, large reforms aimed at centralized coordination of different service providers, such as the integration of the Norwegian welfare administration, have been labeled post-NPM reforms by some researchers. The implication of all these parallel tendencies is that the institutional and organizational landscape surrounding the work situations of employees in the public sector have become increasingly complex, some call them hybrid, putting a variety of conflicting pressures on the performance of work within the sector (Christensen & Lægreid 2011, Hasselbladh et al. 2008). In this special issue, we explore some of the consequences of these structural and normative changes on the work of public sector employees in different sectors and contexts (...)